The diversity and abundance of parasites associated with Xenopus laevis (Daudin, 1803) in selected habitats - Crous, Hanre Pieter (University of the Free State, 1999)
The African clawed frog, Xenopus laevis, has been extensively utilised over the years for a variety of research projects. The frog proved particularly useful as parasite study material because of its diverse parasite assemblage. The parasites of Xenopus represent seven major invertebrate groups, and no less than 29 parasite species are found associated with X laevis utilising all organs except the lungs. The rich diversity of Xenopus parasites is related to the fact that the frog is primarily water living, which facilitates parasite transfer. Despite the extensive research that has been done on the parasites of Xenopus, there is little information available on parasite ecology from field based studies. It is known, however, that parasite infection levels are determined by interaction of ecological factors and parasite and host characteristics. Due to the lack of information in this respect, a field based study was undertaken to determine what impact variations in climate, ecology, host size or age, and host sex have on the diversity and infection levels of parasites of X laevis. Two ecologically different localities were chosen for the purpose of the study. Using baited traps, X laevis were collected during different months over a two year period, and the infection levels of the different parasites determined. The infection levels of parasites in hosts of different size and sex were also determined. All the parasites found in the study occurred at both localities, but infection levels sometimes differed significantly. Although the infection levels varied through the time of the study, the seasonal patterns were not always clearly defined. Definite positive or negative correlation between size and infection levels was found for most of the parasites. The relationship between host sex and infection levels was, however, inconclusive. AJthough the parasites of Xenopus have been extensively studied, a new parasite was found in the bile ducts of the frog. The cyclophyllidean plerocercoid, Valipara campylancristrota (Wedl, 1955) (Cestoda: Dilepididae), was originally recorded from the gall bladder of the tench, Tinea tinea. The morphology and life cycle of the parasite was investigated. A juvenile leech found on the external surface of X. laevis. was preliminarily identified as Marsupiobdella africana, a leech known to infect Xenopus.

Die platanna, Xenopus laevis, is deur die jare aangewend vir 'n verskeidenheid navorsingsprojekte. Die padda is veral geskik vir parasitologiese studies as gevolg van 'n diverse parasiet samestelling. Die parasiete van Xenopus verteenwoordig sewe invertebraat groepe, en nie minder as 29 parasiet spesies word geassosieer met X. laevis. Parasiete word in al die organe behalwe die longe van die platanna gevind. Die feit dat Xenopus waterlewend is dra by tot die ryk samestelling van parasiete omdat dit parasiet oordrag fasiliteer. Ten spyte van die uitgebreide navorsing wat al op die parasiete van Xenopus gedoen is, is inligting ten opsigte van natuurlike parasiet ekologie beperk. Dit is egter bekend dat die infeksie vlakke van parasite beïnvloed word deur die interaksie van ekologiese faktore, en kenmerke van die parasiet en gasheer. As gevolg van die gebrek aan inligting in die veld, is 'n studie gebasseer op veldwerk gedoen om te bepaal watter effek variasie in klimaat, ekologie, gasheer grootte of ouderdom, en die geslag van die gasheer op die diversiteit en infeksie vlakke van parasiete van X laevis het. Die parasiete van X laevis in twee lokaliteite wat ekologies verskil is bestudeer. Platannas is versamel met behulp van fuike gedurende verskillende maande oor 'n periode van twee jaar, en die infeksie vlakke van verskillende parasiete bepaal. Die infeksie vlakke in gashere van verskillende grootte en geslag is ook bepaal. Al die parasiete wat gedurende die huidige studie gevind is het in beide lokaliteite voorgekom, maar die infeksie vlakke het soms betekenisvol verskil. Alhoewel die infeksie vlakke gevarieer het deur die loop van die studie, was seisoenale patrone nie altyd duidelik nie. Betekenisvolle korrelasies tussen die grootte van die gasheer en infeksie vlakke is vir meeste parasiete gevind. Die verhouding tussen infeksie vlakke en die geslag van die gasheer was egter onbeslis. Alhoewel die parasiete van Xenopus al deeglik bestudeer is, is 'n nuwe parasiet in die galbuise van die padda gevind. Die lintwurm larf, Valipara campylancristrota (Wedl, 1955) (Cestoda: Dilepididae) was oorspronklik gevind in die galblaas van die seelt, Tinea tinea. Die morfologie en lewensiklus van die parasiet is ondersoek. 'n Onvolwasse bloedsuier wat op die eksterne oppervlak van X laevis gevind is, is voorlopig geïdentifiseer as Marsupiobdella africana, 'n bloedsuier wat bekend is van Xenopus.
Keywords: Frogs -- Parasites; Xenopus laevis -- Parasites; Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 1999